Rancang Bangun Aplikasi Mobile SiTANDES: Sistem Peminjaman Alat Pertanian Desa Kampunganyar Banyuwangi - Tsalis Rahmad Darmawan; Jauhari Achmad Pradana; Wahyu Setiawan; Alfi Kurinita Widianti; Natasya Ika Marshanda; Hendra Maulana (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The development of digital technology has opened up opportunities to improve the efficiency of agricultural services, including in Kampunganyar Village, Banyuwangi, which has been carried out manually, making it prone to delays and recording errors. To address these issues, the SiTANDES (Sistem Tani Desa) mobile application was developed using Java programming language, Firebase as the database, and XML for the interface with an Agile Scrum approach. System testing was conducted through blackbox and User Acceptance Test (UAT) involving 10 respondents. Test results showed a 100% success rate for application functions in the Black-Box test and a 92% user acceptance rate in the User Acceptance Test, indicating that all features functioned according to user needs. With the implementation of SiTANDES, the tool lending process has become faster, more efficient, and more transparent, supporting the transformation of village agricultural services toward a more modern and information technology-based system.